America and the eastern question - Harlan, Dora Inez (My University, 1908)
Introduction: The Russo-Japanese war lasting from 1905-1906 calls attention once more to the orient and to the far eastern questions. Although at the close of the late war this question seemed settled, this was not the case. The question that was settled was one of land supremacy, but now a far more important one has developed; that of commercial and political supremacy...
Citation: Harlan, Dora Inez. America and the eastern question. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: War; United States; Asia; Graduating theses; Senior theses; Theses